THE INFLUENCE OF THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM ON THE ACHIEVEMENT AND LEARNING SPIRIT OF STUDENTS OF AL AZHAR MEDAN'S LEADING HIGH SCHOOL IN 2022/2023 - Ulyta Khairina; Inayah Nabilah; Nawira Zaid; Ahmad Raushan Fikri; Rahma Suci Ramadhani; Ayu Astuti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
"Kurikulum Merdeka" (Independent Curriculum). This paper looks at how the Merdeka Curriculum was developed and implemented in an attempt to raise the standard of instruction at SMA Unggulan Al-Azhar Medan using policy analysis and pertinent theoretical frameworks. In order to understand the goals of the policy, the tactics used, and its effects on the caliber of education, we gather and examine pertinent policy documents, literature evaluations, and pertinent research findings. Our research pinpoints important elements that affect the Merdeka Curriculum's success, including the function of educators and a well-organized curriculum. Furthermore, we identify implementation issues encountered while putting the Merdeka Curriculum into practice and offer suggestions for its advancement and enhancement. In addition to providing insights for education to improve the quality of learning at SMA Unggulan Al-Azhar Medan, this research advances our qualitative understanding of the Merdeka Curriculum as an educational strategy.